The concept of “Object-image” revisited through the interactive-film installation “Sense of Place” - Caires, C. S; Estadieu, G (Besides the Screen 2020, 2020)

Radial String Chimes: A Behavioural Driven Tangible Instrument Derived from Networked Music Performance Practices - Barbosa, Alvaro; Olga Ng Ka Man, Sandra; Estadieu, G (Ubimus 2023, 2023)
Research in ubiquitous networked music systems has unveiled the potential of behavioural-driven interaction interfaces as an effective model to cope with network communication delays in remote musical performances. Most of the techniques developed under these premises are based on digital music interfaces implemented on laptop computers or tablet devices, where a certain degree of gestural control comes as an added dimension. The purpose of this paper is to present an implementation of such type of interfaces in the form of a physical tangible musical instrument, contemplating multiple expressive possibilities. This is viable at the current stage of technological development thanks to leveraging 3D printing and laser cutting technologies for effective prototyping and testing of such a device. The paper seeks to demonstrate that this approach opens a wide range of possibilities for creating musical instruments with versatility and expressiveness beyond what is usually accomplished in traditional instruments. This implementation, entitled “Radial String Chimes,” is presented with its advantages, the challenges it faces, and the methods used to create it. Finally, the paper will offer suggestions for further developing such an instrument to unlock its potential.

Hacking: Toward a Creative Methodology for Cultural Institutions - Estadieu, G; Caires, C. S (2018)